The privateer - Doohan, James; Stirling, S. M. (Riverdale, New York : Baen Publishing, 1999)
Sentenced to desk duty after an unorthodox but successful maneuver, flight engineer Peter Raeder takes a risky assignment on the fringes of Federation space rather than languish away in an office.
Keywords: Flight engineers -- Fiction; Science fiction